An Initiative for Flotel and Botel Through Cooperative Tourism: A Feasibility Study and The Financial Support of Cooperative Banks - Muhammed Anas.B; Sini.V (Journal of Advanced Research in Accounting and Finance Management, 2026)
Tourism in Kerala, known as “God’s Own Country", has long thrived on its unique geography, rich cultural heritage, and biodiversity. The state’s extensive coastline, interlaced with rivers, backwaters, and beaches, provides an exceptional environment for innovative tourism models such as flotels (floating hotels) and botels (boat hotels). These ventures offer immersive experiences that blend hospitality, mobility, and proximity to nature, contributing to sustainable tourism and regional development. In recent years, the state has witnessed a surge of interest in cooperative tourism initiatives—an alternative paradigm that emphasises collective ownership, participatory management, and community benefit. Kerala’s robust network of cooperative banks provides a promising financial infrastructure for supporting such projects, especially where traditional investors may hesitate due to the unique risks and capital requirements of floating hospitality ventures. Despite the potential, the implementation of flotel and botel operations in Kerala’s beach tourism zones faces challenges: technical, environmental, regulatory, social, and financial. Conducting comprehensive feasibility studies, as established in knowledge-based systems and infrastructure projects, is essential for ensuring the viability, sustainability, and scalability of these cooperative tourism models. 1, 2 This research paper examines the feasibility of flotel and botel operations in Kerala, focusing on their adaptation to cooperative tourism models supported by cooperative banks. It synthesises frameworks from knowledge-based feasibility studies, packaged software implementation, and infrastructure development to propose a structured approach for evaluation, implementation, and management. The discussion is grounded in lessons from related domains, highlighting the interplay between community participation, technology, financial innovation, and operational resilience.